EFEK TOKSISITAS FRAKSI ETIL ASETAT AKAR SENGGANI (Melastoma affine D.Don ) PADA ORGAN HEPAR, GINJAL DAN TESTIS - Moch Saiful Bachri (Pharmaciana, 2011)
Melastoma affine (MA) is a medicinal plant commonly found in south East Asia and China. The aim of the study is to investigate the toxicity effect of MA toward vital organs. Thirty two Wistar adult male rats were divided into five groups consisting of six animals each the rats in group except control group, eight animals. The rats in group I (control) were administered 0.5% CMC Na orally, while CMC Na suspension of ethyl acetate fraction of MA root (62.5, 125, 250,and 500 mg/kg body weight) were given to the II, III, IV and V groups, respectively. The CMC Na suspensions of ethyl acetate fraction of MA root were administered for 22 days. Rats were sacrificed at the 23th day. Liver, kidney, testis were collected for histopathological observation. The observation result on liver and kidney showed no difference compare to control groups, meanwhile on testis, the administration of ethyl acetate fraction of MA root at dose (250, 500 mg/kg body weight) caused necrosis on seminiferus tubules and decreasing sperm counting. The conclusion, administration of ethyl acetate fraction of MA root caused toxicity effect on testis with necrosis on seminiferus tubules.